Developing word-consciousness through learning Latin and Greek morphemes (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article consideres, analyzes and classifies Latin-Greek affixes and roots, which are the main components of morphemes of English scientific and technical terms that require memorization for successful translation and interpretation. Innovativeness of this study is in grounding the necessity for students to understand – "feel" the internal structure and semantics of terms and "construct" a word with meaningful morphological elements without need to "learn by heart" lexical units unclear for them.
Keywords: Latin-Greek affixes; components of morphemes; morphological elements